PENGARUH PROFITABILITAS, LEVERAGE, UKURAN PERUSAHAAN DEWAN KOMISARIS TERHADAP PENGUNGKAPAN ISR PADA PERUSAHAAN MANUFAKTUR DALAM ISSI - Fatma Eka Widiyanti; Nani Septiana (Derivatif : Jurnal Manajemen, 2021)
The purpose of this study was to determine the effect of Profitability, Leverage, Company Size and Company Age on Islamic Social Reporting on Manufacturing Companies in the Indonesian Sharia Stock Index (Empirical Study of Manufacturing Companies Listed on BEI 2018). This type of research is a quantitative study with a research population of 121 companies listed on the Indonesian Sharia Stock Index (ISSI). Only 70 samples are used related to predetermined criteria and only one year of research is conducted, namely in the period 2018. Company data seen from the company's financial statements published by the Indonesia Stock Exchange (BEI) are tested using the SPSS version 20 program. The results showed that there was a positive effect on the Board of Commissioners' size on the disclosure of Islamic Social Reporting on Manufacturing Companies in the Indonesian Sharia Stock Index. While the variables of Profitability, Leverage, and Company Size do not affect the disclosure of Islamic Social Reporting on Manufacturing Companies in the Indonesian Sharia Stock Index.Keywords: Profitability, Leverage, Company Size, Board of Commissioners Size, IslamicSocial Reporting